Thapsigargin Induces Apoptosis by Impairing Cytoskeleton Dynamics in Human Lung Adenocarcinoma Cells - Fei Wang; Da-zhong Liu; Hao Xu; Yi Li; Wei Wang; Bai-lu Liu; Lin-you Zhang (The Scientific World Journal)
The objective of this study was performed to investigate the effects of thapsigargin on apoptosis, actin cytoskeletal dynamics, and actin cytoskeletal proteins in human lung adenocarcinoma cell. Thapsigargin is a specific irreversible inhibitor of ER calcium-ATPase, which may promote ER stress by depletion of lumenal calcium stores and show potential to induce cell death. The effects of thapsigargin on the apoptosis in A549 cells were assayed by Hoechst staining. Moreover, the F-actin staining by Rhodamine-phalloidin and RhoA antibody for cytoskeleton organizations were applied to A549 cells. To confirm the impairment of cytoskeletal dynamics treated with thapsigargin, western blots were applied to analyze the protein levels of p-Cofilin-1 (Ser3), Cofilin-1, and pPaxillin (Tyr118), as well as RhoA and pS6 (S240/244). Results suggest that thapsigargin may induce cell death in A549 cells with a time- and dose-dependent manner. The F-actin fibers and RhoA signals are also reduced with a time- and dose-dependent manner by thapsigargin treatment. The phosphorylation forms of Cofilin-1 and paxillin are attenuated by 1 μM thapsigargin treatment for 24 h. These alternations may be caused by the inhibition of of mTORC1 activities (indicated by pS6 (Ser240/244)) and RhoA pathways after thapsigargin treatment. The present findings highlight important roles of calcium entry in cytoskeleton organization and apoptosis in human lung adenocarcinoma cells and will help to set a stage to the clinical treatment of cancer cell metastasis.